2020
DOI: 10.1007/s12110-020-09368-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Individual Mortality Experience on Out-of-Wedlock Fertility in Eighteenth- and Nineteenth-Century Krummhörn, Germany

Abstract: Life history theory predicts that exposure to high mortality in early childhood leads to faster and riskier reproductive strategies. Individuals who grew up in a high mortality regime will not overly wait until they find a suitable partner and form a stable union because premature death would prevent them from reproducing. Cox proportional hazard models were used to determine whether women who experienced sibling death during early childhood (0–5 years) reproduced earlier and were at an increased risk of givin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…This finding is in line with numerous data (e.g., Chisholm et al, 2005; Dunkel et al, 2015; Međedović, 2019; Sheppard et al, 2016; Webster et al, 2014); showing that a harsher, riskier, and more depriving environment is related to fast life history dynamics, marked by enhanced reproductive output, earlier reproduction, and higher number of children. Furthermore, the result is congruent with the hypothesis and empirical findings that mortality rates are the key environmental characteristics which trigger a fast life history pathway (Belsky et al, 2012; Bereczkei & Csanaky, 2001; Bulley & Pepper, 2017; Ellis et al, 2009; Guégan et al, 2001; Low et al, 2013; Pink et al, 2020; Störmer & Lummaa, 2014; Zhang & Zhang, 2005). Hence, the motivation to have the first child earlier in life could be an adaptive response to the ecology characterized by elevated mortality rates - delaying reproduction could be highly costly to fitness in a harsh environment since individuals may die before leaving descendants.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding is in line with numerous data (e.g., Chisholm et al, 2005; Dunkel et al, 2015; Međedović, 2019; Sheppard et al, 2016; Webster et al, 2014); showing that a harsher, riskier, and more depriving environment is related to fast life history dynamics, marked by enhanced reproductive output, earlier reproduction, and higher number of children. Furthermore, the result is congruent with the hypothesis and empirical findings that mortality rates are the key environmental characteristics which trigger a fast life history pathway (Belsky et al, 2012; Bereczkei & Csanaky, 2001; Bulley & Pepper, 2017; Ellis et al, 2009; Guégan et al, 2001; Low et al, 2013; Pink et al, 2020; Störmer & Lummaa, 2014; Zhang & Zhang, 2005). Hence, the motivation to have the first child earlier in life could be an adaptive response to the ecology characterized by elevated mortality rates - delaying reproduction could be highly costly to fitness in a harsh environment since individuals may die before leaving descendants.…”
Section: Discussionsupporting
confidence: 86%
“…Many authors believe that the relations between a harsh environment and accelerated life history dynamics are mainly due to mortality rates (Belsky et al, 2012; Ellis et al, 2009) 1 . The available data shows that when the local mortality rates are higher (or conversely—with lower life expectancy) individuals tend to reproduce earlier in their lifetime—the findings are congruent both at the individual and population level (Bulley & Pepper, 2017; Low et al, 2013; Pink et al, 2020; Störmer & Lummaa, 2014). There are similar associations between mortality and fertility: individuals who experienced higher mortality rates tend to have a higher number of offspring (Bereczkei & Csanaky, 2001; Guégan et al, 2001; Zhang & Zhang, 2005).…”
Section: Local Mortality As An Environmental Trigger For Fast Life Hi...mentioning
confidence: 91%
“…Our results indicate that exposure to harsh environmental conditions such as famine and crop failure during the first 5 years of life are associated with accelerated life history, in this case earlier marriage. A link between exposure to high mortality and faster life history has been demonstrated for preindustrial and industrial populations [2,3,10,13]. Recent studies have also shown that earlier marriage is associated with exposure to harsh early childhood conditions [1].…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies indicate the effects of high mortality environments in early childhood on marriage and reproductive behaviour [1][2][3]. Life-history theory (LHT) predicts that harsh and uncertain living conditions accelerate maturation to compensate for the probability of fitness failure due to extrinsic risk such as predation and diseases [4] and density-dependent mortality (mortality at all ages is regulated by the density of the population e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Their limited life experience and lack of a helping hand and resources created a risky environment for their children. Offspring that survived in such circumstances followed faster and riskier reproductive strategies, creating similar risk factors among their offspring (Pink, Willführ, Voland, & Puschmann, 2020).…”
Section: Bridal Pregnancies Out-of-wedlock Fertility and Extra-pair P...mentioning
confidence: 99%